Beyond Musical Talent: The Role of Professional Networks in Musicians’ Career Development in Jakarta - Hanorsian, Anastasia Enike; Septiani, Dina; Yunita, Febri Rizma; Paramitha, Kalingga Wenna Ferliqueena; Wahdah, Nikmatul Bahril (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
The growth of the creative economy sector in Indonesia, particularly the music industry, has created a dynamic and competitive environment for musicians in Jakarta. While professional networking is essential for career development, the relationship between musicians’ network usage and career achievement requires further exploration. A qualitative methodology incorporating case studies and thematic analysis was adopted for this study. The study involved a key informant, a professional musician with ten years of experience in Jakarta's music industry. The data gathering process integrated semi-structured interviews alongside social media and document observations. The theoretical framework combined Social Capital Theory and Systems Theory Framework. The study revealed that musicians' career development in Jakarta follows a five-point evolution of social capital: from initial formation relying on bonding capital to portfolio optimization through bridging capital. The interplay among individual, social and environment systems defines key success factors. The research identified three key mechanisms: strategic network formation, collaboration opportunity utilization, and industry dynamics adaptation. Professional networking contributes to career success through reciprocity principles, professional credibility, and adaptive capabilities. The findings demonstrate that successful career development in Jakarta's music industry requires a holistic approach integrating networking strategies with professional growth. The study contributes to understanding how social capital operates in creative industries where boundaries between systems are fluid. These insights are valuable for developing support systems that facilitate inclusive growth in Jakarta's music ecosystem.